The effect of Eurasian Economic Union on trade of Kazakhstan: impact evaluation using the Synthetic Control Method - B. M. Mukhamediyev; Z. S. Temerbulatova; G. K. Ilyashova (Экономика: стратегия и практика, 2020)
Within the framework of integration processes, the trade policies of countries significantly affect the competitiveness of both a single country and the entire integration association. The article provides the evaluation of impact of the Eurasian Economic Union on bilateral trade between Kazakhstan and other member countries of the integration bloc. The aim of the study is to analyze the trade benefits for Kazakhstan after joining the EAEU. The synthetic control method was used. The method is aimed at assessing the effects of the impact using a small number of cases as an example of modeling their quantitative indicators in a hypothetical situation where there was no impact. For modeling data from Kazakhstan and 40 donor pool countries for 1995-2018 were collected. Based on the data, a synthetic counterfactual unit, which best resembles the characteristics of the Kazakhstan, was constructed. As a result of the study, it was determined that bilateral trade flows of Kazakhstan with the EAEU countries in 2018 would have been 18.5 less if Kazakhstan had not joined the EAEU. Also, according to a similar method, an assessment of bilateral trade of Kazakhstan with each EAEU country was carried out separately.